The organisation of dairy farming in the Waikato, New Zealand - Stephens, Frank Burcon (Massey University, 1931)
The present study is an attempt to combine a descriptive account of the technical and financial organisation of Waikato Dairy Farms with an analytical discussion of the factors affecting efficient butterfat production. Management is perhaps the greatest need in the Dairying Industry today. While there is evident a "Desire to know" how to overcome the present difficulties, there is still a great deal of attachment to the routine of habit and custom. This fact is frequently lost sight of and the popular descriptions of farming in New Zealand generally err by discussing farming practice in terms of the best farmers. In the present essay an attempt is made to discuss things as they are and to indicate, where possible, the lines on which advance is being made. [From Preface]
Best copy available due to the condition of the original.
Keywords: Dairy farming; New Zealand; Waikato; Economic aspects; Dairy farms; Management